Dinamika Pembangunan Sumber Daya Manusia (SDM) terhadap Perekonomian dengan Kontribusai Pendapatan Asli Daerah (PAD) sebagai Pemoderasi - Maha Yoga, Gede Agus Dian (Universitas Batanghari Jambi, 2024)
The vulnerability of Bali's economy, which only depends on the tourism sector during the Covid-19 pandemic, has given rise to the idea of economic transformation to develop other sectors. In this effort, human development is a key factor as a major economic actor. Human Development Index (HDI) as an indicator of human resource quality is thought to have a positive influence on the economy as seen from Gross Regional Domestic Product (GRDP) at constant prices. Original Local Government Revenue (OLGR) as financial capital is considered capable of strengthening empowerment programs and policies that directly touch the community and downstream can strengthen the economy. The data used is secondary data for the 2013-2022 period obtained from Regencies and Cities in Bali Province (panel data). This research was tested using Econometric Views (Eviews) software (panel data regression). The analysis techniques used include descriptive statistics, panel data model analysis, classical assumption tests, interaction tests or Moderated Regression Analysis (MRA) and hypothesis testing with analysis of the coefficient of determination and t test. The aim of the research is to determine the effect of HDI on GRDP and to find out whether OLGR is able to moderate the influence of HDI on GRDP. The results show that HDI has a significant positive effect on GRDP. This means that increasing HDI will have a positive impact on increasing GDP. OLGR strengthens the positive influence of HDI on GRDP. This means that OLGR is able to strengthen and have an impact on human resource development and ultimately increase GDP growth which is an indicator of regional economic growth. Suggestions that can be given from the results of human resource investment research can be a priority so that regional communities can become the driving force of the regional economy. It is hoped that the use of OLGR for empowerment programs and policies that touch the community can be implemented more optimally so that it can improve the quality of human resources and have an impact on positive economic growth.